The thin line between transitional justice and memory activism: the case of the German and British ‘pardons’ for convicted homosexuals - Caroli, Paolo (International journal of transitional justice, 2018)
In 2017 the British and German parliaments adopted laws in order to pardon those convicted when homosexuality was criminalized. This article compares the two laws and the respective social and legal contexts in which each was adopted, highlighting their peculiarities. Thereafter, the two laws are categorized by discussing two working hypotheses. The first considers them as reparatory measures of transitional justice. The second associates them with various private or social ventures, very different in content, motivations and impact. The hypothesis is that behind these initiatives a common implicit attitude may be perceived: a desire to amend the past in the light of current values. Finally, some sceptical thoughts about the future are presented, related to the possibility that these laws may constitute the beginning of a new legislative trend aimed at removing the effects of past criminal trials.